Intrapartum Fetal Surveillance: Review of Three National Guidelines - Hill, James B.; Chauhan, Suneet P.; Magann, Everett F.; Morrison, John C.; Abuhamad, Alfred Z. (American Journal of Perinatology, 2012)
Evidence-based guidelines regarding intrapartum fetal surveillance from three countries (United States, Canada, and Australia/New Zealand) were reviewed. The similarities in the three national guidelines (purported etiology, management of periodic changes, and intermittent auscultation for low-risk women) are understandable. Differences in recommendations (role of fetal admission test, amnioinfusion for variable decelerations, scalp pH, umbilical arterial acid-base status, and education in interpretation of fetal heart tracing) are not explained. The likelihood of recommendations being categorized as level A differed for the countries: United States, 41% (7/17); Canada, 18% (3/17); and Australia and New Zealand, 17% (2/12). Only one publication was cited by all three guidelines. To avoid confusion and possibly enhance their quality, national guidelines should acknowledge the presence of others on the same topic, and if there are differences then provide explanations for dissimilarities.
Keywords: fetal heart rate monitoring; practice bulletin; guidelines; intrapartum